2021
DOI: 10.1038/s41598-021-82143-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV induces airway basal progenitor cells to adopt an inflammatory phenotype

Abstract: Despite the introduction of anti-retroviral therapy, chronic HIV infection is associated with an increased incidence of other comorbidities such as COPD. Based on the knowledge that binding of HIV to human airway basal stem/progenitor cells (BC) induces a destructive phenotype by increased MMP-9 expression through MAPK signaling pathways, we hypothesized that HIV induces the BC to express inflammatory mediators that contribute to the pathogenesis of emphysema. Our data demonstrate that airway BC isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 100 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…This has been achieved in cross-sectional studies, most recently with the demonstration that airway basal stem (progenitor) cells isolated from virally suppressed HIV-positive but not HIV-negative non-smokers spontaneously release inflammatory mediators. 10 Thus, the study demonstrated that HIV is associated with faster lung function decline independent of smoking or legacy effects from before initiation of antiretroviral therapy, and further supports a role of chronic immune activation in this association. The phenotypic difference between declines in HIV-related pulmonary function and declines related to smoking provide further support that the evidenced effects on pulmonary health were driven largely by HIV status.…”
Section: Lung Function Declines More Rapidly In Treated Hiv-positive People Than In Hiv-negative Peoplesupporting
confidence: 61%
“…This has been achieved in cross-sectional studies, most recently with the demonstration that airway basal stem (progenitor) cells isolated from virally suppressed HIV-positive but not HIV-negative non-smokers spontaneously release inflammatory mediators. 10 Thus, the study demonstrated that HIV is associated with faster lung function decline independent of smoking or legacy effects from before initiation of antiretroviral therapy, and further supports a role of chronic immune activation in this association. The phenotypic difference between declines in HIV-related pulmonary function and declines related to smoking provide further support that the evidenced effects on pulmonary health were driven largely by HIV status.…”
Section: Lung Function Declines More Rapidly In Treated Hiv-positive People Than In Hiv-negative Peoplesupporting
confidence: 61%
“…PLWH on HAART therapy have chronic lung inflammation 48 – 55 , contributing to HIV-associated aging, lung injury and tissue damage 2 , 21 – 23 , 50 , 53 , 55 , 56 . Our recent studies demonstrate that HIV binding to airway BC increased secretion of MMP-9 and inflammatory mediators 27 , 28 and BC from PLWH showed increased release of IL-8 IL-1β, ICAM-1 and GM-CSF 27 , 28 . These mediators and proteases such as MMPs are collectively known as senescence associated secretory phenotypes (SASP) 57 , 58 .…”
Section: Discussionmentioning
confidence: 91%
“…Other possible mechanisms of HIV-associated lung aging include direct effect of HIV or viral proteins and opportunistic infections 2 , 23 , 47 . Our prior studies demonstrated that HIV can induce BC to express inflammatory mediators and MMP-9 27 , 28 . We demonstrate that disordered epithelium observed in PLWH is closely associated with BC senescence due to the adverse effects of HAART on BC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations